Interaction of drivers and barriers of sustainable property management practice in shopping malls in Lagos, Nigeria - Nyirenda, Lumbani B.; Ayedun, Caleb A.; Musonda, Innocent; Iroham, Chukwuemeka O.; Olukanni, David O.; Okagbue, Hilary I.; Samuel, Olugbemisola W.; Nto, Sunday E. (Frontiers in Built Environment, 2025)
Extant studies on sustainable property management (SPM) are yet to be reported for shopping malls in developing countries. Shopping malls play a vital role in commercial activities in developing countries. This study investigates the strategies and the interaction of the drivers and barriers to SPM practice being adopted in the management of three randomly selected shopping malls in Lagos, Nigeria. The primary data utilized were elicited with the aid of a questionnaire served on 130 tenants of the three shopping malls. The obtained data were analyzed using statistical tools such as mean ranking, frequency distribution, exploratory factor analysis (EFA), confirmatory factor analysis (CFA) and mediation analysis. LED energy saving bulbs (90%) and green leasing (6.9%) are the most and least adopted features while using environmental cleaning procedures (83%) and adopting green leasing (36.4%) are the top and least SPM adopted strategy. Health and wellbeing of occupants (88.4%), cost savings (87%) and regulatory requirements (85%) were ranked the top three drivers while EFA grouped the factors into 2: direct and indirect. Financial and economic barrier (4.2/5) were top while cultural factors (3.97/5) were the least. The interactions of the latent barrier factors were exposed by the CFA and mediated regression models. In conclusion, this article explored SPM within shopping mall operations, presenting evidences that, while beneficial in reinforcing the relevance of sustainability in the real estate sector, ultimately contributes modestly to the broader academic discourse on the subject.